MECHANISMS OF ACUTE FATTY LIVER PREGNANCY: AN UP-DATE - Паличева, Елена Ивановна; Артымук, Дмитрий Анатольевич (Mother and Baby in Kuzbass, 2018)
The aim of the study was to study the basic mechanisms of formation of acute fatty liver dystrophy in pregnant women based on the analysis of modern databases.Materials and methods. The information bases of the system Cochrane, HINARY, PubMed were estimated. Key words (words for search): «acute fatty liver disease of pregnancy» and «biochemical mechanism». The depth of the search was 5 years (2014-2018).Results. 1139 publications were found. Meets the selection criteria: 37 publications. At the heart of pathogenesis, mitochondrial cytopathies and anomalies in mitochondrial β-oxidation are generally recognized. The enzyme, long chain 3-hydroxyacyl coenzyme A-dehydrogenase (LCHAD), is a key part of the mitochondrial trifunctional protein. It is proved that about 20 % of newborns born to mothers with AFLP have defects of β-oxidation and lack LCHAD because of a mutation on one or both alleles of the α-subunit of trifunctional protein. Unoxidized fatty acids are actively involved in the synthesis of triacylglycerides (TAG) via phosphatidic acid. Phosphatidic acid is also a metabolite for the synthesis of phospholipids with lipotropic factors (serine, choline, methionine, B12, etc.). However, in conditions of active fetal growth, their active use for plastic reactions is taking place, and the mother's liver experiences their deficiency. Another reason for the accumulation of TAG in the liver of a pregnant woman may be a disruption of the synthesis of the transport forms of lipoproteins and, accordingly, the blocking of their exit from the hepatocytes.Conclusions. Recent evidence suggests a fetal-maternal interaction causing acute fatty liver of pregnancy. Approximately one in five women who develop AFLP may carry an LCHAD-deficient fetus. Screening the newborn at birth in pregnancies complicated by AFLP for this fatty acid oxidation disorder can be lifesaving and may allow for genetic counseling in subsequent pregnancies.
Keywords: acute fatty liver; pregnancy; long chain 3-hydroxyacyl coenzyme A-dehydrogenase deficiency